Mortality and anti-feedant effect of nanoemulsion formulations of rotenone against Spodoptera litura - Adam, Normala (2016)
The toxicity of nanoemulsion of rotenone F1, F2, F3 in comparison with crude extract of rotenone was evaluated against Spodoptera litura (Lepidoptera : Noctuidae) for their mortality and antifeedant activity. All formulations containing 1% of rotenone were used in this study. Test on mortality and antifeedant activity of S. litura were determined by leaf dip method ( Karunaratne & Arukwatta, 2008). The area of leaf discs I. aquatica used was 60 cm². There were five treatments (218.4, 163.8, 109.2 and 54.6ppm) with five replications for each treatment used in this research study. The leaf discs dipped in distilled water were used as control. The mortality of S. litura was recorded at 24, 48 and 72 hours after treatments. Antifeedant activity was recorded after the 3rd instar larvae were exposed to treated leaf disc for 24 hours. The mortality results indicated that nanoemulsion formulations F1, F2, F3 showed highly significant different with crude extract but no significant different between the nanoemulsion formulations F1, F2, F3 was observed. Among the formulations, LC50 values of nanoemulsion formulations were lower than crude extract indicating they were effective against S. litura by causing high mortality even at low concentration. Nanoemulsion formulation F1 was found to show a highly significant in reduction in food consumption. When compared with other formulations, nanoemulsion F1 showed higher antifeedant effect on the larvae at all concentrations tested. At concentration 273, 218.4 and 163.8 ppm, the leaf area consumed were 15.29, 18.01, 24.45cm2 respectively 24 hours after treatment.